Openness and economic growth in developing and OECD countries - Idris, Jamilah; Yusop, Zulkornain; Habibullah, Muzafar Shah; Lee, Chin (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This study explores the linkage between openness and economic growth in 86 developing and OECD countries from 1977 to 2011, using the Generalized Method of Moments (GMM) estimations. The empirical findings reveal that openness generally promotes economic growth in developing and OECD countries. This is consistent with the endogenous growth theory which states that growth increases with trade openness.